Systematic Review of Professional Liability when Prescribing Β-Lactams for Patients with a Known Penicillin Allergy. (4th October 2017) - Jeffres, Meghan; Hall-Lipsy, Elizabeth; King, S Travis; Cleary, John
Abstract: Background: Patients labeled as penicillin allergic are more likely to receive second line non-β-lactam antibiotics, experience higher rates of treatment failure, and incur higher antibiotic costs. Fear of litigation has been identified as a reason clinicians avoid using β-lactams in a patient with a penicillin allergy. The systematic review objective is to describe medical negligence and malpractice cases in which known penicillin allergy patients received a β-lactam and experienced an adverse reaction. Methods: Lexis-Nexus and Google Scholar were used to identify relevant legal cases. Variables collected from each case included date of publication, legal jurisdiction, date of injury, plaintiff and defendant demographics, health care setting, plaintiff clinical outcome, and legal outcome. Results: Twenty-seven unique cases met inclusion criteria. The earliest case was published in 1959 and the most recent in 2013. The highest number of cases filed ( n = 7) occurred in the most recent 10 year segment, from 2005 to 2015. Eighteen cases involved the receipt of a penicillin-based antibiotic; of these cases with a known legal outcome, the plaintiff (patient) prevailed or settled in 3 cases and defendants (providers) prevailed in 7 cases. Seven cases involved the receipt of a cephalosporin; of these cases with a known legal outcome, the plaintiff settled with physicians prior to trial in 1 case and defendants prevailed in 3 cases. Two cases involved the receipt of a carbapenem. Defendants prevailed in 1 case and the legal outcome of the other case is unknown. In cases where the defense successfully moved for summary judgment, judges cited a lack of scientific evidence demonstrating that a cephalosporin or carbapenem were contraindicated for a patient with a penicillin allergy. Conclusion: The cases with published legal outcomes found limited professional liability and identify clear precedence for clinicians who prescribed cephalosporins or carbapenems to a patient with a known penicillin allergy. These results should decrease litigation fears of providers and risk managers within healthcare systems. Disclosures: All authors: No reported disclosures.